2006
DOI: 10.1215/s0012-7094-06-13213-1
|View full text |Cite
|
Sign up to set email alerts
|

Rational Cherednik algebras and Hilbert schemes, II: Representations and sheaves

Abstract: Abstract. Let Hc be the rational Cherednik algebra of type A n−1 with spherical subalgebra Uc = eHce.Then Uc is filtered by order of differential operators with associated graded ring gr Uc = C[h ⊕ h * ] W , where W is the n-th symmetric group. Using the Z-algebra construction from [GS] it is also possible to associate to a filtered Hc-or Uc-module M a coherent sheaf Φ(M ) on the Hilbert scheme Hilb(n).Using this technique, we study the representation theory of Uc and Hc, and relate it to Hilb(n) and to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(101 citation statements)
references
References 35 publications
5
96
0
Order By: Relevance
“…This also clarifies the relationship between the two approaches, for example showing that the characteristic cycles defined independently in [GS2] and [GG] are actually equal, thereby confirming a conjecture of [GG].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…This also clarifies the relationship between the two approaches, for example showing that the characteristic cycles defined independently in [GS2] and [GG] are actually equal, thereby confirming a conjecture of [GG].…”
supporting
confidence: 76%
“…The key to [GS1,GS2] is the construction of a Z-algebra B = i≥j≥0 ( c+i P c+j ) endowed with a natural matrix multiplication. The ring B has a natural filtration induced from the differential operator filtration Γ on D(h reg ) * W , and the main result [GS1,Theorem 1.4] showed that if c + i is good for all i ∈ N, then the associated graded ring gr Γ B of B is the Z-algebra associated to Hilb n C 2 .…”
Section: 4mentioning
confidence: 99%
“…This is true when ℓ = 1 by [23,Theorem 6.7] and it has been established for n = 1 and any ℓ in [30]. In 10.3…”
mentioning
confidence: 75%
“…By an important result of Heckman-Opdam, see [9], eH 1,c (S n )e − is a (U 1,c (S n ), U 1,c+1 (S n ))-bimodule and one can show it induces an equivalence The advantage of this construction is that one can apply Haiman's work directly. This leads in [46] to the calculation of the characteristic cycle of any object from O c (S n ), i.e. the support cycles in Hilb n (C 2 ) of the degeneration of the corresponding objects in X c ; one can also show that the image in X c of the U 1,c (S n )-module eH 1,c (S n ) is a deformation of the Procesi bundle P on Hilb n (C 2 ).…”
Section: Reduction and Localisationmentioning
confidence: 99%